EVOLUTION OF R&D MANAGEMENT: CHALLENGES FOR INDONESIAN AGRICULTURAL AND ESTATE CROPS SECTORS - Hermawati, Wati; Kusbiantono, Kusbiantono; Setiawan, Sigit; Surminah, Iin (Journal of S&T Policy and R&D Management, 2013)
Development of the management of research and development (R&D) has experienced very rapid progress, especially in relation to win business opportunities at the global level. The evolution of R&D management at the global level now has up to the fifth-generation led to the sixth generation, which is characterized by the magnitude of dependence on the information and communication technology as well as the application of the principles of knowledge management in R&D activities. In order to know the development of R&D management in Indonesia, the study focused on the agricultural and estate crops sectors. The analysis is performed against several criteria of operational R&D Management, which are characterized by their respective R&D generation. Results of the study showed that the majority of the operational criteria of R&D management in agriculture and estate crops sectors in Indonesia mostly are still at the third generation. Challenges of R&D facing in agriculture and estate crops sectors in entering a higher R&D generation is increasing capacity of researchers to become more professional as well as a self-managing knowledge workers, focusing on the user or providing solutions for all user problemsÃ¢â¬â¢, develop a broader job networking (network), an R&D organization that fosters continuous learning and transnational oriented by developing a more open communication and use ICT as an intelligent knowledge processors, as well as implement collaborative strategies in daily activities, and resulting patent/licences.